PENGENDALIAN PERSEDIAAN SUKU CADANG NUT DENGAN MENGGUNAKAN METODE KLASIFIKASI ABC DAN MODEL Q BACK ORDER DI PT FGH - Tandiansyah, Tantan; Nasrullah, Rizky; Fauzi, Muchammad (CV SWA Anugerah, 2025)
This study aims to analyze and optimize the management of nut spare parts inventory at PT FGH using the ABC Classification method and the Q Back order Model. ABC classification is used to group 20 types of spare parts based on the value of fund absorption and frequency of demand, so as to determine management priorities. The analysis results show that 70.66% of the funds are allocated to category A, which includes components with high consumption value and significant demand frequency. Meanwhile, the Q Back order Model is applied to calculate the optimal ordering lot size (q0), safety stock (ss), reorder point (r), and service level (η), with a high level of inventory cost efficiency. The results of applying the Q Back order Model show total cost savings for category A, with the lowest total inventory cost of Rp113,591,283 and the highest of Rp528,899,608. The combination of the ABC Classification method and the Q Back order Model provides an effective solution in managing inventory strategically, minimizing costs, reducing the risk of stock shortages, and maintaining a smooth production process. The implementation of this method can be a reference for more efficient and sustainable inventory management at PT FGH